Perubahan Struktur Sosial, Aktivitas Ekonomi dan Budaya Lokal Akibat Perkembangan Wisata Bahari di Desa Tapulaga Kecamatan Soropia Kabupaten Konawe - Mursin Mursin (Prodi PGSD Unsultra, 2026)
The development of marine tourism has become a driving factor in changes in the lives of coastal communities, not only economically but also in the local social and cultural structures. Tapulaga Village, Soropia District, Konawe Regency, is one of the coastal areas experiencing marine tourism development due to increasing tourist visits and the development of supporting infrastructure. This study aims to analyze changes in the social structure, economic activities, and local culture of the community due to the development of marine tourism in Tapulaga Village. The study used a qualitative approach with ethnographic methods. Data were collected through participant observation, in-depth interviews with community leaders, tourism businesses, fishermen, the village government, and documentation. Data analysis was conducted through interactive data reduction, data presentation, and conclusion drawing. The results show that the development of marine tourism has transformed the community's social structure through livelihood diversification, increased social mobility, and the formation of new economic groups oriented towards the tourism service sector. From an economic perspective, the community has experienced increased income through various businesses, such as culinary, gazebo rentals, villas and boats, trade, and other tourism services. Meanwhile, in the cultural aspect, there have been changes in social interaction patterns, lifestyles, and cultural values ​​due to increased contact with tourists. However, tourism development also provides opportunities for preserving local culture through the development of traditional culinary arts, arts, and various community traditions as tourist attractions. This study concludes that the development of marine tourism has had a multidimensional impact on the Tapulaga Village community, necessitating sustainable tourism management that involves the local community, strengthens social institutions, and preserves coastal culture and the environment.